Simulasi Reaktor Elektrokoagulasi Plate Column Berpengaduk Secara Kontinu Berbasis CFD Pada Pengolahan Limbah Cair Kelapa Sawit - Amelisa, Tika; Amri, Idral; Sunarno, Sunarno (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
Palm oil mill effluent continues to increases in line with the increase in palm oil production in Indonesia. Therefore, another alternative technology is needed such as the continuous stirred plate column electrocoagulation. Many laboratory scale studies have been carried out. CFD simulation is used as an advanced technology in treating palm oil mill effluent. The objective for this study is to Obtain optimum equipment design conditions for an electrocoagulation reactor using CFD, see the phenomena that occur due to the influence of flow rate variables and electrode distance, and see the trajectory of the solution profile in the reactor. This study was done based on Software Ansys Fluent Version 16.2 64 program with the k-ɛ standard turbulence model. After doing pre-processing, solving and post-processing steps in simulation, then the result of this simulation is analyze. The simulation results obtained were optimal conditions at a flow rate of 0.4 L/min and a plate distance of 2 cm with consecutive residence time values of 2.77; 4.0; and 3.88 hours. In the variation in the influence of flow rate, it can be seen that the phenomenon that the faster the flow rate, the greater the turbulence. In the variation of electrode distance, it can be seen that the phenomenon of electrode distance affects the level of turbulence in the reactor, too far a distance can cause the flow to be too slow. The latter is that the CFD model can accurately predict the trajectory of the solution profile in the stirred plate column electrocoagulation reactor.